Amelioration of Endotoxin-Induced Acute Lung Injury and Alveolar Epithelial Cells Apoptosis by Simvastatin Is Associated with Up-Regulation of Survivin/NF-kB/p65 Pathway - Nežić, Lana; Amidžić, Ljiljana; Škrbić, Ranko; Gajanin, Radoslav; Mandić, Danijela; Dumanović, Jelena; Milovanović, Zoran; Jaćević, Vesna (International journal of molecular sciences, 2022)
Disruption of the alveolar−endothelial barrier caused by inflammation leads to the progression of septic acute lung injury (ALI). In the present study, we investigated the beneficial effects of simvastatin on the endotoxin lipopolysaccharide (LPS)-induced ALI and its related mechanisms. A model of ALI was induced within experimental sepsis developed by intraperitoneal injection of a single non-lethal LPS dose after short-term simvastatin pretreatment (10−40 mg/kg orally). The severity of the lung tissue inflammatory injury was expressed as pulmonary damage scores (PDS). Alveolar epithelial cell apoptosis was confirmed by TUNEL assay (DNA fragmentation) and expressed as an apoptotic index (AI), and immunohistochemically for cleaved caspase-3, cytochrome C, and anti-apoptotic Bcl-xL, an inhibitor of apoptosis, survivin, and transcriptional factor, NF-kB/p65. Severe inflammatory injury of pulmonary parenchyma (PDS 3.33 ± 0.48) was developed after the LPS challenge, whereas simvastatin significantly and dose-dependently protected lung histology after LPS (p < 0.01). Simvastatin in a dose of 40 mg/kg showed the most significant effects in amelioration alveolar epithelial cells apoptosis, demonstrating this as a marked decrease of AI (p < 0.01 vs. LPS), cytochrome C, and cleaved caspase-3 expression. Furthermore, simvastatin significantly enhanced the expression of Bcl-xL and survivin. Finally, the expression of survivin and its regulator NF-kB/p65 in the alveolar epithelium was in strong positive correlation across the groups. Simvastatin could play a protective role against LPS-induced ALI and apoptosis of the alveolar−endothelial barrier. Taken together, these effects were seemingly mediated by inhibition of caspase 3 and cytochrome C, a finding that might be associated with the up-regulation of cell-survival survivin/NF-kB/p65 pathway and Bcl-xL.
Keywords: pneumocyty; Simvastatin; Caspase 3; Lipopolysaccharides; Up-Regulation; kaspasa 3; cytochromy c; alveolar epithelial cells; plíce; Survivin; lipopolysacharidy; Acute Lung Injury; upregulace; simvastatin; NF-kB/p65; Alveolar Epithelial Cells; Lung; lidé; akutní poškození plic; Humans; NF-kappa B; Cytochromes c; apoptóza; apoptosis; Endotoxins; endotoxiny; survivin; Apoptosis